The Role of Affiliates in Consumer Purchase Interest in Online Shops in the Digital Business Era - Erna Indasari (Penerbit Hellow Pustaka, 2023)
The increasing development of science and technology today has brought very significant changes in the sales process. No more than that, the sales process is facilitated by the existence of digital systems, especially online. Online shops require sellers to apply the latest strategies and innovations to attract buyers to buy the products traded. One strategy that can be used by sellers is to market the products they sell using affiliate services as well as affiliate marketing techniques. Affiliate participation in the buying and selling process has proven to have a significant influence on the ongoing online buying and selling process. This is what will be the object of research using internet searching and library research methods. This method will collect data through internet media and library sources such as journals, articles and other related sources that will also be included. The results obtained through this research show that the existence of Affiliate Marketing played by Affiliators assisted by marketing intermediaries through social media has an impact on online sales because the Affiliators can influence the buying interest of consumers